2013
DOI: 10.1017/jfm.2013.375
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the suppression of viscous fingering in elastic-walled Hele-Shaw cells

Abstract: Recent experiments by Pihler-Puzovic et al. (Phys. Rev. Lett., vol. 108, 2012, article 074502) have shown that the onset of viscous fingering in circular Hele-Shaw cells in which an air bubble displaces a viscous fluid is delayed considerably when the top boundary of the cell is replaced by an elastic membrane. Non-axisymmetric instabilities are only observed at much larger flow rates, and the large-amplitude fingers that develop are fundamentally different from the highly branched fingers in rigid-walled ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 45 publications
5
54
0
Order By: Relevance
“…ForV > 300 ml.min −1 the system was found to be unstable to non-axisymmetric fingering instabilities studied earlier by Pihler-Puzović et al (2012; forV < 50 ml.min −1 , the air-liquid interface remained circular but drifted slowly across the cell in a rigid-body mode (with unit azimuthal wavenumber). This latter instability is due to the finite extent of the HeleShaw cell, and is always present for rigid-walled cells, even when the flow rate is so small that all other non-axisymmetric modes are suppressed (Pihler-Puzović et al 2013). At larger flow rates, the geometry of the elastic-walled cell is drastically different, and this mode is no longer observed to be unstable.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…ForV > 300 ml.min −1 the system was found to be unstable to non-axisymmetric fingering instabilities studied earlier by Pihler-Puzović et al (2012; forV < 50 ml.min −1 , the air-liquid interface remained circular but drifted slowly across the cell in a rigid-body mode (with unit azimuthal wavenumber). This latter instability is due to the finite extent of the HeleShaw cell, and is always present for rigid-walled cells, even when the flow rate is so small that all other non-axisymmetric modes are suppressed (Pihler-Puzović et al 2013). At larger flow rates, the geometry of the elastic-walled cell is drastically different, and this mode is no longer observed to be unstable.…”
Section: Methodsmentioning
confidence: 96%
“…The Föppl-von Kármán equations were discretised by a mixed finite-element method in which we approximated the vertical displacements, ζ, the Airy stress functions φ, and their respective Laplacians by piecewise quadratic basis functions, defined on threenoded, one-dimensional elements. Again, we omit details but refer to Pihler-Puzović et al (2013) for a more detailed discussion of the implementation. The fully-coupled, implicit discretisation of the fluid and solid equations produces a large system of nonlinear algebraic equations at each timestep.…”
Section: Membrane Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, interest in the control of the properties of this instability by mechanical, [1][2][3][4][5][6][7] thermal, [8][9][10][11][12][13] or chemical [14][15][16][17][18][19][20][21][22][23][24] ways for instance are of constant interest in the literature. Numerous experimental and theoretical works have already shown that the properties of the fingers (such as their mixing length or their area) can be strongly affected by in situ changes in the viscosity field distribution induced by gradients of temperature or composition in the solutions.…”
Section: Introductionmentioning
confidence: 99%